2017
DOI: 10.1007/s13577-017-0160-3
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative medicine for Parkinson’s disease using differentiated nerve cells derived from human buccal fat pad stem cells

Abstract: The purpose of this study was to evaluate the utility of human adipose stem cells derived from the buccal fat pad (hBFP-ASCs) for nerve regeneration. Parkinson's disease (PD) is a neurodegenerative disorder characterized by progressive death of dopaminergic neurons. PD is a candidate disease for cell replacement therapy because it has no fundamental therapeutic methods. We examined the properties of neural-related cells induced from hBFP-ASCs as a cell source for PD treatment. hBFP-ASCs were cultured in neurog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 39 publications
1
10
0
1
Order By: Relevance
“…To confirm the purity of cells, SCGNs cultured for 3 days were immunostained with NF-200 antibody and TH antibody. 19 As shown in Figure 5 , immunofluorescence analyses showed that the cells cultured in our study were positive for both NF-200 and TH antibodies. This finding proves that the cells assessed were sympathetic neurons with catecholamine secreting function.…”
Section: Resultssupporting
confidence: 52%
“…To confirm the purity of cells, SCGNs cultured for 3 days were immunostained with NF-200 antibody and TH antibody. 19 As shown in Figure 5 , immunofluorescence analyses showed that the cells cultured in our study were positive for both NF-200 and TH antibodies. This finding proves that the cells assessed were sympathetic neurons with catecholamine secreting function.…”
Section: Resultssupporting
confidence: 52%
“…These cells can differentiate toward multiple lineages, such as osteogenic [ 2 ], chondrogenic [ 3 ], adipogenic [ 4 ], cardiac [ 5 ], epidermal [ 6 ], and neurogenic [ 7 ] lineages. hASCs are used widely in the field of regenerative medicine, including to promote bone regeneration [ 2 ], tooth and periodontal regeneration [ 8 ], cartilage regeneration [ 9 ], wound healing [ 6 , 10 ], and nerve regeneration to cure Parkinson’s disease [ 11 ], as well as to suppress aging [ 10 ]. Due to the advantages of the autologous source of these cells and their relative abundance and ease of isolation, hASCs have also been widely used in the fields of plastic surgery and regenerative medicine [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…hDPSCs were differentiated by culturing them in differentiation medium consisting of DMEM/F12 supplemented with 5% FBS, 10 μM MEM-NEAAs, 2 mM glutamate (Nacalai tesque), 10 nM all trans-retinoic acids (Merck, Darmstadt, Germany), 50 μM ascorbic acid (Tokyo Chemical Industry, Tokyo, Japan), 5 μM insulin (Cell Signaling Technology, Danvers, MA, USA), 10 nM dexamethasone (FUJIFILM, Tokyo, Japan), 20 nM progesterone (Tokyo Chemical Industry), 20 nM estradiol (FUJIFILM), 50 ng/mL nerve growth factor (NGF; Alomone Labs, Jerusalem, Israel), 10 ng/mL thyroxine (T4; FUJIFILM), 50 U/mL penicillin, 50 μg/mL streptomycin, and 0.25 μg/mL Fungizone as described previously [ 42 ]. For fluorescence measurements, cells were cultured in glass-bottom dishes with or without grids (AGC techno glass).…”
Section: Methodsmentioning
confidence: 99%
“…These studies indicate that hDPSCs have the potential to differentiate toward neuron-like cells that function in the CNS. On the other hand, some studies have reported that hDPSCs also differentiated toward bipolar shape neuron-like cells similar to peripheral neurons [ 36 , 42 ]. However, whether the differentiated hDPSCs have peripheral neuron-like characteristics have not been investigated.…”
Section: Introductionmentioning
confidence: 99%